Three essays on homeownership and financial well-being - Rollins-Koons, Ashlyn (My University, 2024)
This dissertation uses multiple techniques and frameworks to examine how housing tenure decisions relate to different components of financial well-being using primary and secondary data. Buying or maintaining a home has become increasingly expensive and out of reach for many individuals in the U.S. Research is needed to understand how mortgage and non-mortgage-holding homeowners and renters experience financial strain and residential satisfaction, and what other housing factors help explain these relationships. Both objective and subjective measures of financial well-being provide a comprehensive view of how U.S. individuals are faring in their homes. Essay one examined whether housing adjustments — specifically residential mobility and residential adaptation — are related to objective indicators of financial strain. Using the 2022 Survey of Consumer Finances, the sample was restricted to 2,832 respondents who indicated their primary residence was an owned house. The findings suggested that residential adaptation was negatively related to financial strain. In essay two, an experimental design was used to determine whether housing adjustments (residential mobility, residential adaptation, and family adaptation) were related to residential satisfaction and financial strain. This study also looked at the association between financial strain and residential satisfaction. Primary data was collected through Amazon’s Mechanical Turk (MTurk) from homeowners in the U.S. with at least one financially dependent child. The final sample size was 933. The findings indicated that family adaptation and residential mobility are related to residential satisfaction, but not financial strain. Financial strain was positively related to residential satisfaction. Essay three explored the mediating effects of residential satisfaction and housing cost burden for three different housing tenures (non-mortgage holding homeowners, mortgaged homeowners, and renters). This study collected primary data through MTurk and used structural equation modeling to examine these relationships. The results indicated that homeowners with mortgages and renters had less financial well-being than homeowners who did not have mortgages. It also appeared that these relationships were fully mediated by objective and subjective housing cost burden and residential satisfaction. Both measures of housing cost burden were negatively related to financial well-being, while residential satisfaction was positively related to financial well-being. The findings from these three essays help explain why homeowners may experience increased financial well-being from their housing tenure. This dissertation provides evidence that housing adjustments may not impact financial strain (at least for those who can afford to make the adjustment in the first place) and do improve residential satisfaction. These studies also provide more context for why homeownership is often found to have a positive relationship to financial well-being. Having a mortgage, someone’s realized or perceived housing cost burden, and their residential satisfaction all play an important role.
Keywords: Homeownership; Financial well-being; Financial strain; Residential satisfaction; Housing cost burden; Renter